PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU DALAM MELAKSANAKAN KURIKULUM 2013 : (Studi di Kecamatan Merauke, Kabupaten Merauke) - Khoriyatun; Bambang Santoso Haryono (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
The purpose of this study was to analyze and describe the influence of teacher competence with five variables, namely motivation; skills, knowledge and ideas; learn to be independent; interactive competence; awareness and computer skills on teacher performance in implementing the 2013 curriculum in elementary schools in Merauke District, Merauke Regency. The sampling technique used purposive sampling with the Slovin formula, the number of samples was 84 teachers. Collecting data using a Likert scale questionnaire. Data analysis and hypothesis testing in this study were using multiple linear regression. The results of data analysis: a) That motivation; skills, knowledge and ideas; learn to be independent; interactive competence; awareness and computer skills partially have a positive and significant effect on teacher performance, and b) Collectively motivation; skills, knowledge and ideas; learn to be independent; interactive competence; awareness and computer skills have an effect of 52% on teacher performance and have a positive and significant effect.